A randomised, factorial trial to reduce arterial stiffness independently of blood pressure: Proof of concept? The VaSera trial testing dietary nitrate and spironolactone. Issue 5 (22nd February 2020) - Mills, Charlotte E.; Govoni, Virginia; Faconti, Luca; Casagrande, Maria‐Linda; Morant, Steven V.; Crickmore, Hannah; Iqbal, Fahad; Maskell, Perry; Masani, Alisha; Nanino, Elisa; Webb, Andrew J.; Cruickshank, J. Kennedy
Abstract : Aims: To test if spironolactone or dietary nitrate from beetroot juice could reduce arterial stiffness as aortic pulse wave velocity (PWVart), a potential treatment target, independently of blood pressure. Methods: Daily spironolactone (≤50 mg) vs doxazosin (control ≤16 mg) and 70 mL beetroot juice (Beet‐It ≤11 mmol nitrate) vs nitrate‐depleted juice (placebo; 0 mmol nitrate) were tested in people at risk or with type‐2 diabetes using a double‐blind, 6‐month factorial trial. Vascular indices (baseline, 12, 24 weeks) were cardiac–ankle vascular index (CAVI), a nominally pressure‐independent stiffness measure (primary outcome), PWVart secondary, central systolic pressure and augmentation. Analysis was intention‐to‐treat, adjusted for systolic pressure differences between trial arms. Results: Spironolactone did not reduce stiffness, with evidence for reduced CAVI on doxazosin rather than spironolactone (mean difference [95% confidence interval]; 0.25 [−0.3, 0.5] units, P = .080), firmer for PWVart (0.37 [0.01, 0.7] m/s, P = .045). There was no difference in systolic pressure reduction between spironolactone and doxazosin (0.7 [−4.8, 3.3] mmHg, P = .7). Circulating nitrate and nitrite increased on active vs placebo juice, with central systolic pressure lowered −2.6 [−4.5, − 0.8] mmHg, P = .007 more on the active juice, but did not reduce CAVI, PWVart or peripheral pressure. Change in nitrate and nitrite concentrations were 1.5‐fold [1.1–2.2] and 2.2‐fold [1.3, 3.6] higher on spironolactone than on doxazosin respectively; both P < .05. Conclusion: Contrary to our hypothesis, in at‐risk/type 2 diabetes patients, spironolactone did not reduce arterial stiffness, rather PWVart was lower on doxazosin. Dietary nitrate elevated plasma nitrite, selectively lowering central systolic pressure, observed previously for nitrite.